Food system actors engaged in the cocreation of agroecological innovations - results of year 2 engagement in eight countries - Staiger-Rivas, S.; Orjuela-Ramirez, G. (International Water Management Institute, 2023)
The CGIAR initiative on Agroecology is actively engaging with food system actors (FSA) in eight countries (Burkina Faso, India, Kenya, Lao PDR, Peru, Senegal, Tunisia, and Zimbabwe), particularly to codesign, test, and adapt agroecological innovations, both technological and institutional, from food production to consumption. At the core is the necessity to generate scientific evidence that shows how agroecological principles applied in different socio-ecological systems are better able to provide equity, productivity, economic and environmental benefits than alternatives, including the status quo. The engagement takes place in Agroecological Living Landscapes (ALLs) that are formed in selected territories of each country with diverse stakeholders, including farmer associations or communities, researchers from multiple disciplines, extensionists, private companies, international and national non-governmental organizations as well as local, regional, and national policymakers. The establishment of ALLs does not follow a standard methodology: Each country’s context leads to a different agroecological transition pathway(s) and multi stakeholder approaches. The engagement of food system actors is addressed in the monitoring, evaluation, learning and impact assessment (MELIA) component of the initiative. Country teams collect and report data quarterly based on the following definitions: FSA are defined as private sector agents, policymakers, and female and male small-scale farmers, researchers, communities, investors. They engage with the initiative when they participate in meetings and activities that aim at assessing, co-designing and testing agroecological innovations at farm, market and policy levels. The co-creation process consists in FSA working together and having an equal voice in the activities that aim at developing culturally relevant innovations. Agroecological innovations in turn are of technological and institutional nature and concern the broad range of Agroecological principles (HLPE, 2019). This summary analyzes the data from 2022, and data collected from January to October 2023. It includes seven countries, the data from Senegal missing as it is the latest country to join the Initiative. A report covering all eight countries and the entire two-year span will be published early 2024.